Nonsteroidal anti‐inflammatory drugs in acute viral respiratory tract infections: An updated systematic review - Nima Azh; Farzaneh Barzkar; Nogol Motamed‐Gorji; Parmida Pourvali‐Talatappeh; Yousef Moradi; Roya Vesal Azad; Mitra Ranjbar; Hamid Reza Baradaran (Wiley, 2022)
Abstract In this systematic review, we aimed to assess the efficacy and safety of nonsteroidal anti‐inflammatory drugs (NSAIDs) in treating respiratory tract infections in adults and children. PubMed, Scopus, Web of Science, Cochrane, and Embase databases were searched. A total of 34 randomized clinical trials were included in this systematic review. We assessed the risk of bias of all included studies using the Cochrane tool for risk of bias assessment. The evidence on ibuprofen, naproxen, aspirin, diclofenac, and other NSAIDs were rated for degree of uncertainty for each of the study outcomes and summarized using the grading of recommendations assessment, development, and evaluation (GRADE) approach. Our findings suggest that high‐quality evidence supports the use of NSAIDs to reduce fever in both adults and children. However, the evidence was uncertain for the use of NSAIDs to reduce cough. Most studies showed that NSAIDs significantly relieved sore throat. The evidence for mortality and oxygenation is limited. Regarding the adverse events, gastrointestinal discomfort was more frequently reported in children. For adults, our overall certainty in effect estimates was low and the increase in gastrointestinal adverse events was not clinically significant. In conclusion, NSAIDs seem to be beneficial in the outpatient management of fever and sore throat in adults and children. Although the evidence does not support their use to decrease mortality nor improve oxygenation in inpatient settings, the use of NSAIDs did not increase the rate of death or the need for ventilation in patients with respiratory tract infections. Further studies with a robust methodology and larger sample sizes are recommended.